Welfare assessment of horses and mules used in commercial beef cattle ranches in Brazil - Zuliani, Laura [UNESP]; Trindade, Pedro Henrique Esteves; Paranhos da Costa, Mateus José Rodrigues [UNESP] (Elsevier, 2023)
This study aimed to identify, among the equine welfare indicators included in two available protocols (Assessment Protocol for Horses and AWIN - Welfare Assessment Protocol for Horses), those suitable to assess the welfare of ranch horses and mules in commercial beef cattle ranch in Brazil and report the welfare status of these animals when kept under such management and working conditions. Twenty-two equine animal-based welfare indicators were evaluated in 84 horses and 51 mules from seven commercial ranches located in the state of Mato Grosso, Brazil. Most of the indicators showed no or little changes from an acceptable standard of animal welfare, defined when the welfare indicators were scored 0 or when a small number of animals were scored 1, for variables scored from 0 to 2. Those indicators which indicated frequent welfare problems (forced approach test, hoof problems, body condition score, integument alterations, lesions at mouth corners, and orbital tightening) were subjected to a principal component analysis (PCA). Differences between ranches were compared by the Kruskal-Wallis test, and between mules and horses, the Mann-Whitney test was used. The first principal component of the PCA indicated that forced approach test and integument alterations were directly associated with each other and inversely associated with body condition score, lesions at mouth corners, hoof condition, and orbital tightening. Ranch 1 showed a higher score on the forced approach test than Ranch 5, which may be related to variations in their handling routines. Mules showed a greater avoidance response during the forced approach test, while horses had a higher incidence of hoof problems, which may be associated with the differences in behavior and anatomy of these animals. We conclude that, except for facial expression indicators, all other animal-based welfare indicators were useful for assessing the welfare of ranch horses and mules, but that they were not sufficient to carry out a complete welfare assessment of these animals, since it lacks proper environmental-based indicators. Thus, we consider this study as a first step towards the development of a specific protocol to assess the welfare of ranch horses and mules. Additionally, our results clearly show that most of the welfare problems identified in this study can be prevented or mitigated by training cowhands on how correctly raise and handle the ranch horses and mules under their care.
Keywords: Animal-based indicators; Avoidance behavior; Body condition; Health indicators; Ranch work